Integrated Tourism Policy Based On Local Wisdom For Economic Recovery Post-Covid-19 Pandemic With The Concept Of Penta Helix Strategy - Julianti, Lis; Suharyanti, Ni Putu Noni; Darma Pratiwi, Agustina Ni Made Ayu (Faculty of Law, Universitas Pekalongan, 2024)
This study aimed to identify and formulate the model of integrated tourism policy based on local wisdom for economic recovery from post covid-19 pandemic. The method of this research was empirical legal research by using primary data sources in form of an interview which was analyzed qualitatively and displayed descriptively. The finding of this research showed that the design of the integrated policy in tourism was conducted by designing a policy formulation in which the policy formulation design was taken from strategic issues related to tourism including internal and external conditions in implementing tourism policy, and the analysis of the previous policies was conducted including analysis of policy and analysis for policy.